Applying direct language learning strategies when teaching English - Belmaz, Yaroslava; Horovenko, Oksana (My University, 2023)
The article deals with the issue of language learning strategies. Different approaches to the definition and classification of LLS are studied. The authors of the article focus on applying direct learning strategies in the process of teaching English. The goal of the present research was to prove the effectiveness of direct language learning strategies to form students’ lexical competence. In the article, the methods and techniques used in the process of the experiment are presented. The result shows that direct learning strategies in teaching English have a positive effect on students’ achievements. Authors’ findings also confirm that a system of practical tasks based on LLS got positive feedback from the participants of the experiment
Belmaz Ya. Applying direct language learning strategies when teaching English / Yaroslava Belmaz, Oksana Horovenko // Scientific Journal of Khortytsia National Academy, 2023. – Issue 8. - P. 49–56
Keywords: стратегії вивчення мови, прямі стратегії, когнітивна стратегія, стратегія, пов’язана з пам’яттю, стратегія компенсації; language learning strategies, direct strategies, cognitive strategy, memory-related strategy, compensation strategy